Relationship of Sympathetic Dysfunction with Disease Duration In Female Rheumatoid Arthritis Patients - Ferdousi, Sultana; Jahan, Kowser; Begum, Noorzahan (Journal of Bangladesh Society of Physiologist, 2015)
Background: Association of increased cardiovascular morbidity and higher sympathetic activity in patients with Rheumatoid arthritis (RA) has been well recognized. Objective: To assess sympathetic nerve function status in Rheumatoid arthritis patients and its relationship to duration of the disease. Methods: This study was carried out in the dept of Physiology Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during 2010.Sixty female RA patients aged 18-50 years with duration of disease from 1 to 10 years was selected from Rheumatology wing of Medicine OPD of BSMMU. Age and BMI matched female apparently healthy subjects were control. Sympathetic nerve function status was assessed by blood pressure response to orthostatic test and sustained hand grip isometric exercise test. In these two tests, fall in systolic blood pressure (SBP) and rise in diastolic blood pressure (DBP) respectively estimates sympathetic reactivity. For statistical analysis, unpaired students t test and pearsons correlation coefficient test was applied. Results: Mean values of fall of SBP was higher and rise of DBP was lower in RA patients compared to control which was statistically (P<0.001) significant. Again rise of DBP was negatively and fall of SBP was positively correlated with duration of the disease and the relationships were statistically highly significant (p<0.01). Conclusion: The results conclude that sympathetic reflex response was reduced in RA which was deteriorated with duration of disease. Bangladesh Soc Physiol. 2015, June; 10(1): 17-20